Bridging theory, policy, and practice: Stakeholder engagement in Ghana's NPEC - Richard Lionel Gorni; Asep Suryana; Eka Prihatin (Inovasi Kurikulum, 2024)
Ghana's education system is transforming significantly by implementing the National Pre-Tertiary Education Curriculum Framework (NPECF), emphasizing critical thinking and problem-solving skills over traditional rote learning. Translating these ambitious policy goals into effective classroom practices within a centralized system presents challenges. This research addresses this challenge through stakeholder analysis, examining how the involvement of policymakers, educators, parents, and local communities can bridge the gap between NPECF's theoretical ideals and practical classroom application. The research identifies potential roadblocks and opportunities for successful curriculum adoption by analyzing these diverse perspectives. Understanding the interactions and influences among policymakers, teachers, parents, and communities is crucial for transitioning smoothly from rote learning to a student-centered approach. This analysis highlights areas where stakeholders might need additional support or resources to embrace the new curriculum effectively. Ultimately, the findings can inform future educational reforms in Ghana and similar contexts, paving the way for a more effective and engaging learning experience for all students.